(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Despite increasing in industrial and agricultural activities near Dadin Kowa Dam, limited data exist on heavy metal contamination in its aquatic ecosystem. This study investigates metal concentration in commonly consumed fish species in northern parts of Nigeria and many parts of Africa to assess potential health risks. Heavy metals in fish originate from industrial discharge, agricultural runoff, and natural geological processes, necessitating continuous monitoring. Chronic exposure to Pb, Cd, As, Fe, Cu, and Ni is linked to neurological damage, renal failure, and carcinogenic effects, making their presence in food sources a serious concern. AAS analysis was performed using certified reference materials, and calibration was validated with standard solutions to ensure accuracy. The planet catfish was found to have high levels of lead (0.0237 mg/100g), while Cadmium contents in Red-tailed Synodontis were alarming (0.0560 mg/100g), beyond safety limits and potentially harmful to health. The greatest arsenic level was found in African Cat Fish (0.0655 mg/100g), which suggests that long-term exposure should be avoided. ANOVA results (p < 0.05) indicate significant variation in heavy metal accumulation between species, identifying Planet Catfish and Red-tailed Synodontis as the most contaminated. To minimize exposure risks, regular monitoring programs, public health advisories, and dietary guidelines on fish consumption should be implemented. Findings are compared against WHO/FAO (2021) guidelines for permissible heavy metal concentrations in fish.